2016
DOI: 10.1038/srep21090
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal vascularity index as a measure of vascular status of the choroid: Measurements in healthy eyes from a population-based study

Abstract: The vascularity of the choroid has been implicated in the pathogenesis of various eye diseases. To date, no established quantifiable parameters to estimate vascular status of the choroid exists. Choroidal vascularity index (CVI) may potentially be used to assess vascular status of the choroid. We aimed to establish normative database for CVI and identify factors associated with CVI in healthy eyes. In this population-based study on 345 healthy eyes, choroidal enhanced depth imaging optical coherence tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
634
7
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 554 publications
(662 citation statements)
references
References 41 publications
(61 reference statements)
18
634
7
3
Order By: Relevance
“…39,40 In their previous publications, authors of both techniques have compared binarized images to the original OCT images and showed that dark area corresponded to lumens of choroidal vessels. 18,19 Both authors have also demonstrated high intragrader and intergrader reliability of their measurements in previous reports. 18,19 Discrepancy in CVI and L/C ratio could be explained by the differences in methodology.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…39,40 In their previous publications, authors of both techniques have compared binarized images to the original OCT images and showed that dark area corresponded to lumens of choroidal vessels. 18,19 Both authors have also demonstrated high intragrader and intergrader reliability of their measurements in previous reports. 18,19 Discrepancy in CVI and L/C ratio could be explained by the differences in methodology.…”
Section: Discussionmentioning
confidence: 65%
“…All statistical analyses were performed using statistical software (SPSS version 20.0; IBM Corp. Armonk, NY, USA) and statistical significance was evaluated at 5% level. 19 (C, F, I) OCT images after binarization using technique proposed by Sonoda et al 18 (A-C) One subject in which choroidal vascularity index (CVI) is similar to luminal/ choroidal ratio (L/C ratio). (D-F) One subject in which CVI is smaller than L/C ratio.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations